2019
DOI: 10.1124/jpet.119.257261
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Intraperitoneal Administration of Low-Concentration Methylcellulose Leads to Systemic Histologic Lesions Without Loss of Preclinical Phenotype

Abstract: Methylcellulose (MC; 0.5% concentration) is commonly used when evaluating investigational agents for efficacy in preclinical models of disease. When administered by the oral (PO) route, MC is considered a Food and Drug Administration "generally recognized as safe" compound. Yet, there is limited data pertaining to the tolerability and impact on model fidelity of repeated intraperitoneal administration of 0.5% MC. Chronic administration of high-concentration MC (2%-2.5%) has been used to induce anemia, splenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Open Field (OF) -In this assay, each mouse was placed into an OF Plexiglass chamber (40L × 40W × 30H cm) equipped with infrared sensors to detect animal movement for 10 min. During the 10-min period, the total distance travelled (cm), vertical activity counts, and horizontal activity counts in both the center and perimeter of the OF were automatically recorded by the computer system, consistent with our reported methods with kindled mice (Barker-Haliski et al, 2016b;Barker-Haliski et al, 2016a;Koneval et al, 2018;Meeker et al, 2019;Koneval et al, 2020).…”
Section: Methodssupporting
confidence: 62%
“…Open Field (OF) -In this assay, each mouse was placed into an OF Plexiglass chamber (40L × 40W × 30H cm) equipped with infrared sensors to detect animal movement for 10 min. During the 10-min period, the total distance travelled (cm), vertical activity counts, and horizontal activity counts in both the center and perimeter of the OF were automatically recorded by the computer system, consistent with our reported methods with kindled mice (Barker-Haliski et al, 2016b;Barker-Haliski et al, 2016a;Koneval et al, 2018;Meeker et al, 2019;Koneval et al, 2020).…”
Section: Methodssupporting
confidence: 62%
“…First, the present protocol does not require chronic ASD administration during the kindling process to elicit pharmacoresistance, unlike our previously developed LTG‐resistant CKM 6 . Repeated administration of formulation vehicles like 0.5% MC may themselves elicit pathological changes 29 ; thus the fact that the presently described pharmacoresistant kindling protocol does not require drug administration is of high value to ASD discovery. Second, the present pharmacoresistant kindling model is characterized by Racine stage seizures that progress through an easily differentiated escalation in seizure severity (ie, Racine stages 1‐5; Figure 2), whereas the 6 Hz CKM elicits early focal seizures that are difficult to differentiate and do not initially present on the Racine scale 5 .…”
Section: Discussionmentioning
confidence: 99%
“…This stimulation intensity was determined to be initially benign and pilot studies of CF-1 mice that were similarly stimulated with a 10-fold reduction in voltage (9.0 V) did not lead to kindled seizures or the expression of Racine stage seizures in over 3 weeks of twice-daily stimulations (not shown). Based on our history with CKM, 13,19,26,28,29 we sought to characterize the pharmacology of this stimulation protocol to determine whether it demonstrated a differentiated profile from traditional 60 Hz kindling (ie, 3 seconds, 3.0 mA stimulation). As noted below, this novel stimulation protocol results in a kindling model that is resistant to several of the ASDs tested.…”
Section: Corneal-kindled Mousementioning
confidence: 99%
“…Numerous studies have demonstrated that mLVs played an important role in maintaining brain tissue homeostasis and dysfunction of mLVs was involved in the progression of neurodegenerative diseases (6,9,27). Dysfunction of mLVs would aggravate deposition of Ab in brain tissue and cognitive impairment in AD mouse model (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%